Postural balance and rifle stability during standing shooting on an indoor gun range without physical stress in different groups of biathletes - Sattlecker, G.; Buchecker, M.; Müller, E.; Lindinger, S. J. (International Journal of Sports Science and Coaching, 2014)
The aim of the current study was to examine postural balance, rifle stability and shooting performance in biathletes, analysing the basic precision shooting skills without physical load in different performance groups. Therefore, kinematic and kinetic data from the World Cup (WC; n = 8), the European Cup (EC; n = 13) and a federal youth athletes` squad (n = 15) were recorded on an indoor shooting range. The participants had to shoot ten 5-shot-clips without physical load. Postural balance and rifle stability were measured by VICON (Oxford, UK) and PEDAR (Munich, Germany) systems over the last 0.6 s before firing. WC and EC groups showed lower body and rifle sway (mainly in cross-shooting direction) compared to youth athletes (p < 0.05). Postural balance and gun stability predominantly in cross-shooting direction were negatively correlated to shooting performance (r = -0.33 to -0.59; p < 0.05). The present data indicate the relevance of low body and rifle sway primarily in cross-shooting direction for a successful basic biathlon standing shooting at rest. Special biathlon specific balance and rifle stability training forms used in basic shooting trainings can be recommended.